Employment Law Based on Civil Law and Common Law Legal Systems - Ade Papa Rihi; Zainal Arifin Hosein (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study discusses the regulation of employment law based on the Civil Law and Common Law legal systems, as well as the fundamental differences between the two legal systems in employment law. In the Civil Law legal system, employment law is generally regulated by laws enacted by the government, with the role of the courts limited to the application of written and codified laws. In contrast, in the Common Law legal system, the regulation of employment law relies more on court decisions and precedents resulting from previous cases, with judges having an important role in forming new legal principles. This study uses a normative legal research method with a statute approach and a conceptual approach to analyze employment law regulations in both legal systems. The results show that the Civil Law system provides more structured and detailed provisions, while the Common Law system tends to be more flexible and relies on litigation and specific court decisions. This study is expected to provide a deeper understanding of the differences in employment law regulations based on the two legal systems.